Three-Dimensional Accuracy of Digital Impression versus Conventional Method: Effect of Implant Angulation and Connection Type - Marzieh Alikhasi; Hakime Siadat; Alireza Nasirpour; Mahya Hasanzade (Hindawi Limited, 2018)
Purpose. The aim of this in vitro study was to compare the accuracy of different implant impression techniques of the maxillary full arch with tilted implants of two connection types. Materials and Methods. Two maxillary edentulous acrylic resin models with two different implant connections (internal or external) served as a reference model. Each model had two anterior straight and two posterior angulated implants. Ninety impressions were made using an intraoral scanner (Trios 3Shape) with scan bodies for digital impression (groups DII and DIE), a custom open tray with additional silicone for the conventional direct group (groups CDI and CDE), and a custom closed tray with additional silicone for the conventional indirect group (groups CII and CIE) from both internal and external models, respectively. A coordinate-measuring machine (CMM) was used to measure linear and angular displacement for conventional specimens. For digital groups, an optical CMM was used to scan the reference model. STL data sets from the digital specimen were superimposed on STL reference data sets to assess angular and linear deviations. Data were analyzed with three-way ANOVA and t-test at α=0.05. Results. There were significant angular and linear distortion differences among three impression groups (P<0.001), angular distortion differences between internal and external connections (P<0.001), and between straight and tilted implants for either linear (P<0.001) or angular (P=0.002) distortion. The type of the connection and implant angle did not have any effect on linear and angular distortion of the digital technique (p>0.05). Minimum angular and linear distortion was seen for tilted implants in DII and DIE groups (0.36° ± 0.37 and 0.16 ± 0.1 mm). Conclusion. Impression techniques (digital versus conventional) affected the transfer accuracy. Digital techniques demonstrated superior outcome in comparison with conventional methods, and the direct technique was better than the indirect conventional technique. Connection type and implant angulation were other factors that influenced accuracy. However, when digital impression was applied, accuracy was not affected by the type of connection and angulation.